2016
DOI: 10.18273/revsal.v48n3-2016003
|View full text |Cite
|
Sign up to set email alerts
|

Initial treatment of combat related limb injuries in Colombia

Abstract: Manejo inicial de lesiones en extremidades asociadas al conflicto armado en ColombiaAlfredo Martínez-Rondanelli ABSTRACT Introduction:Injuries caused by high-energy war weapons are frequent in Colombia. This type of weaponry produces highly complex injuries to the musculoskeletal system that is challenging for health professionals. Objectives: To describe various combat related injuries in Colombia and treatment. Methodology: This is a series of cases from a retrospective cohort including Colombian civilians,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Another important consideration is that the prevalence estimates could have been influenced by the under-representation of only seven studies conducted in developing countries compared to 32 studies conducted in developed countries. Trauma or combat-related amputations are common in some regions in South America, Middle East, and West and Central Africa [ 57 – 59 ]. However, these regions are underrepresented in the body of studies identified by this review.…”
Section: Discussionmentioning
confidence: 99%
“…Another important consideration is that the prevalence estimates could have been influenced by the under-representation of only seven studies conducted in developing countries compared to 32 studies conducted in developed countries. Trauma or combat-related amputations are common in some regions in South America, Middle East, and West and Central Africa [ 57 – 59 ]. However, these regions are underrepresented in the body of studies identified by this review.…”
Section: Discussionmentioning
confidence: 99%